Classroom assessment practices of a pre-university academic in Malaysia: preliminary findings - Ab Hamid, Ahmad Rauyani (2021)
Classroom assessment practices (CAPs) can significantly impact students’ academic success. This study was aimed at exploring CAPs performed by an academic staff at the Centre for Foundation Studies, International Islamic University Malaysia. This grounded-theory study deployed a face-to-face interview in order to gain insights into the informant’s CAPs. A possible theory emerged from this study is that academics constantly refer to internal and external sources when they are uncertain about their CAPs. Since this is a pilot study, a document analysis on relevant documents should be carried out as a means of triangulation in order to increase the credibility of the study. As required by grounded-theory theorists, more participants should be included for theme comparison.